Subacute toxicity study of hibiscus rosa-sinensis l. leaves water extract in Balb/C mice: histopathological assessment - Zulkifli, Azizatul Munawarah (2017)
Hibiscus rosa-sinensis is a glabrous shrub widely cultivated as an ornamental plant. Hibiscus rosa-sinensis is commonly used to treat fever and coughs among ethnics in Malaysia. This study aims to determine toxic dose and histopathological changes on the liver and kidney of BALB/c mice after administration of 50mg/kg, 300mg/kg and 2000mg/kg of Hibiscus rosa-sinensis leaves water extract for a period of 28 days. 24 mice were randomly divided into 4 groups consisting 6 mice per group: 3 mice from both sexes. The control groups received tap water (vehicle). In this experiment, no clinical signs and mortality was observed. Result from weight analysis and food intake analysis showed continuous increase in average body weight and food intake between all group of BALB/c mice throughout the 28days.Histopathological examination of liver revealed mild histopathological changes with significant difference between the groups (p<0.05).The liver in group 2(50mg/kg), group 3(300mg/kg) and group 4(2000mg/kg) showed presence of activated kupffer cell, sinusoidal dilation and karyorrlysis and karyorrhexis. However, histopathological analysis of kidney revealed some abnormality but the abnormality was not significant between the groups. The presence of pyknotic cell were noticed in group 2(50mg/kg) and group 3(300mg/kg). In conclusion, administration of Hibiscus rosa-sinensis water extract had shown mild histopathological changes in liver tissues but no changes in kidney.